Mitigation of Salt Stress in Rice by the Halotolerant Plant Growth-Promoting Bacterium Enterobacter asburiae D2 - Zican Ning; Kexin Lin; Mengya Gao; Xiao Han; Qingjie Guan; Xiang Ji; Shuyu Yu; Lei Lu (MDPI AG, 2024)
Salinity is a major abiotic stress that seriously affects crop growth worldwide. In this work, we aimed to isolate potential halotolerant plant growth-promoting rhizobacteria (PGPR) to mitigate the adverse impacts of salt stress in rice. An isolate, D2, with multiple plant growth-promoting (PGP) characteristics was identified as Enterobacter asburiae D2. Strain D2 could produce indole-3-acetic acid and siderophore. It also exhibited phosphate solubilization and 1-aminocyclopropane-1-carboxylic deaminase activity. Genome analysis further provided insights into the molecular mechanism of its PGP abilities. Strain D2 inoculation efficiently stimulated rice growth under both normal and saline conditions. Compared with the non-inoculated plants, a significant increase in plant height (18.1-34.7%), root length (25.9-57.1%), root dry weight (57.1-150%), and shoot dry weight (17.3-50.4%) was recorded in inoculated rice seedlings. Meanwhile, rice seedlings inoculated with strain D2 showed improvement in chlorophyll and proline content, while the oxidant damage was reduced in these plants in comparison with the control group. Moreover, the K+/Na+ ratio of the inoculated rice seedlings exposed to NaCl and Na2CO3 was higher than that of the uninoculated groups. These results imply that Enterobacter asburiae D2 is a potential PGPR that can be used for alleviation of salt stress in rice.